Reassurance as a key outcome valued by emergency ambulance service users: a qualitative interview study. (10th October 2014) - Togher, Fiona J.; O'Cathain, Alicia; Phung, Viet‐Hai; Turner, Janette; Siriwardena, Aloysius Niroshan
Abstract: Background: There is an increasing need to assess the performance of emergency ambulance services using measures other than the time taken for an ambulance to arrive on scene. In line with government policy, patients and carers can help to shape new measures of ambulance service performance. Objective: To investigate the aspects of emergency ambulance service care valued by users. Design: Qualitative interview study. Setting: One of 11 ambulance services in England. Participants: Twenty‐two users and eight of their spouses ( n  = 30). Results: Users of the emergency ambulance service, experiencing different types of ambulance service response, valued similar aspects of their pre‐hospital care. Users were often extremely anxious about their health, and the outcome they valued was reassurance provided by ambulance service staff that they were receiving appropriate advice, treatment and care. This sense of being reassured was enhanced by the professional behaviour of staff, which instilled confidence in their care; communication; a short wait for help; and continuity during transfers. A timely response was valued in terms of allaying anxiety quickly. Discussion and conclusions: The ability of the emergency ambulance service to allay the high levels of fear and anxiety felt by users is crucial to the delivery of a high quality service. Measures developed to assess and monitor the performance of emergency ambulance services should include the proportion of users reporting feeling reassured by the response they obtained.